Food Quantity and Quality Interactions at Phytoplankton–Zooplankton Interface: Chemical and Reproductive Responses in a Calanoid Copepod - Bi, Rong; Sommer, Ulrich (Frontiers in Marine Science, 2020)
Marine food webs form the major component of the biological pump and play a central role in the global carbon (C) cycle. Understanding the response of particular processes in marine food webs to changing environments is a prerequisite to predict changes in ecological functioning in the future ocean. Here, we experimentally assessed the effects of nitrogen: phosphorus (N:P) supply ratios (the molar ratios 10:1, 24:1 and 63:1) on elemental and biochemical quality of marine phytoplankton Rhodomonas sp., and the interactions between food quantity and quality on stoichiometric C:N:P, fatty acids (FAs) and reproductions in copepods Acartia tonsa. Overall, the stoichiometry of A. tonsa was to some extent homeostatic in response to the changing algal C:N and C:P ratios, with significant changes in C:N ratios of A. tonsa observed, especially under higher food quantities. The relative gross growth efficiencies (GGEs) for C and N (and P) were analyzed, revealing that copepods may achieve homeostasis by lowering the GGE for C while increasing it for the limiting nutrient. Egg production rates in A. tonsa were lowest on nutrient deficient diets under low food quantities. Reduced egg production rates may be attributed to the lowered GGEs for C and reduced transfer efficiency of essential FAs between phytoplankton and copepods, indicating interactive-essential effects of elements and FAs on copepod production. Our results highlight that nutrient deficiency in the environments may reduce energy transfer efficiency at the base of food webs by altering phytoplankton chemical composition, which can interact with food quantity and have implications on food web dynamics in the changing ocean.